Age- and Sex-Specific Analyses of Diet Quality and 4-Year Weight Change in Nonobese Adults Show Stronger Associations in Young Adulthood. Issue 3 (5th November 2019) - Vinke, Petra C; Navis, Gerjan; Kromhout, Daan; Corpeleijn, Eva
ABSTRACT: Background: Although the general importance of diet quality in the prevention of unintentional weight gain is known, it is unknown whether its influence is age or sex dependent. Objective: The aim of this study was to investigate whether the strength of the association between diet quality and 4-y weight change was modified by age and sex. Methods: From the Dutch population-based Lifelines Cohort, 85, 618 nonobese adult participants (age 18–93 y), recruited between 2006 and 2013, were included in the study. At baseline, diet was assessed with a 110-item food-frequency questionnaire. The Lifelines Diet Score, based on international evidence for diet-disease relations at the food group level, was calculated to assess diet quality. For analyses, the score was divided in quintiles (Qs). Body weight was objectively measured at baseline and after a median follow-up of 44 mo (25th−75th percentile: 35–51 mo). In between, body weight was self-reported twice. Linear mixed models were used to investigate the association between diet quality and weight change by sex and in 6 age categories (18–29, 30–39, 40–49, 50–59, 60–69, and ≥70 y). Results: Mean 4-y weight change decreased over age categories. Confounder-adjusted linear mixed models showed that the association between diet quality and weight change was modified by sex ( P -interaction = 0.001). In women, the association was also modified by age ( P -interaction = 0.001). Poor diet quality was most strongly associated with weight gain in the youngest men [Q1 compared with Q5: +0.33 kg/y (95% CI: 0.10, 0.56)] and women [+0.22 kg/y (95% CI: 0.07, 0.37)]. In contrast, in women aged ≥70 y, poor diet quality was associated with greater weight loss [−0.44 kg/y (95% CI: −0.84, −0.05)]. Conclusions: Poor diet quality was related to higher weight gain, especially in young adults. Oppositely, among women aged ≥70 y, poor diet quality was related to higher weight loss. Therefore, a healthful diet is a promising target for undesirable weight changes in both directions.